Exploring the Domains of Gender as Measured by a New Gender, Pain and Expectations Scale - Maryam Ghodrati; David M. Walton; Joy C. MacDermid (Mary Ann Liebert, 2021)
Background: While sex- or gender-based differences in pain expression have been documented, exploration of traditionally genderized traits on pain has been hampered by the lack of strong measurement tools. This study evaluated the structural validity of a 16-item ?Gender personality traits? subscale of a recently developed Gender, Pain and Expectations Scale (GPES). Methods: Data were drawn from an existing database of 248 participants (65.7% female). Maximum likelihood-based confirmatory factor analysis was carried out while considering the conceptual meaningfulness of subscales to evaluate the factor structure identified by these traits. Construct validity was explored using a priori hypotheses regarding anticipated mean differences in scores between biological male and female participants. Results: A meaningful factor structure could not be defined with all 16 items. Through conceptual and statistical triangulation a three-factor structure informed by 10 items was identified that satisfied acceptable fit criteria. The factors were termed ?Emotive,? ?Relationship-Oriented,? and ?Goal-Oriented.? Evidence of construct validity was supported through significant sex-based differences (p???0.02) in the expected directions for all three subscales. Conclusions: Review of the items in the three factors led the researchers to endorse a move away from naming these ?masculine? and ?feminine,? rather focusing on the nature of the traits: ?Relationship-oriented,? ?Emotive,? and ?Goal-oriented.? Implications for researchers conducting sex/gender-based pain research are discussed. Clinical Trial Registration number: NCT02711085.